2009
DOI: 10.1089/lap.2008.0264
|View full text |Cite
|
Sign up to set email alerts
|

What Should Be the Ideal Time for Ischemic Preconditioning in a Laparoscopic Rat Model?

Abstract: Five minutes of the IP model may be as reliable as 10 minutes of the IP model. In that case, 5 minutes of IP can be more suitable in reducing I/R injury in laparoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…Some authors proposed that the diminished renal blood flow during Pp and its return to normal flow after deflation leads to an ischemia and reperfusion injury (3,4,27,28). Hence, Pp would induce changes in podocyte morphology that were not seen in the present study.…”
Section: Discussionmentioning
confidence: 48%
“…Some authors proposed that the diminished renal blood flow during Pp and its return to normal flow after deflation leads to an ischemia and reperfusion injury (3,4,27,28). Hence, Pp would induce changes in podocyte morphology that were not seen in the present study.…”
Section: Discussionmentioning
confidence: 48%
“…9 Diminished renal blood flow during pneumoperitoneum and its return to normal flow after deflation have been shown to lead to ischaemia-reperfusion injury. [28][29][30] Such ischaemia-reperfusion injury has been associated with increased levels of reactive oxygen species in the kidney, 31 where glomeruli are considerably more sensitive to oxidative injuries than any other segments of the nephron. 32 Elevated calcium ion levels are a key factor in apoptosis and necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, 5-or 10-min-ischemia followed by a reperfusion of 5-10 min is used most commonly [1,48] . Arioz et al [49] published a study in 2009, and compared LPC 5-min with LPC 10-min. As a result, they concluded that 5 min of pneumoperitoneum, and subsequent 5 min of desufflation, seems to be comparable to 10 min of inflation and desufflation periods, against laparoscopic IRI.…”
Section: Role Of Laparoscopic/robotic Ipcmentioning
confidence: 99%
“…As a result, they concluded that 5 min of pneumoperitoneum, and subsequent 5 min of desufflation, seems to be comparable to 10 min of inflation and desufflation periods, against laparoscopic IRI. So they suggested it to be more practical for clinical use [49] . It is important to mention that to date there is no human studies to assess the role of described laparoscopic/robotic IPC.…”
Section: Role Of Laparoscopic/robotic Ipcmentioning
confidence: 99%